2019
DOI: 10.1002/psb.1753
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of hypertension in primary care

Abstract: Hypertension is a major modifiable risk factor for cardiovascular disease, but conflicting opinions remain about optimal blood pressure targets. This article discusses the various definitions of hypertension, provides guidance on management in primary care and advises when referral to secondary care is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Independent β-arrestin signaling of G-proteins is also induced by this [9,28,29]. This SIIstimulated signaling affirms that the conformations of the β-arrestin coupling receptor and the G-protein-activating receptor are distinct [8]. In contrast, β-arrestin's effects in isolated adult mouse cardiomyocytes suggested that, in isolated cardiac myocytes, the contraction of β-arrestin signaling is induced via SII, indicating the cardiac role of βarrestin-biased ligands [30].…”
Section: Side Effects Of Conventional Antihypertensive Drugs and An Insight On The Process Of New Cardiac Drug Discoverysupporting
confidence: 58%
See 3 more Smart Citations
“…Independent β-arrestin signaling of G-proteins is also induced by this [9,28,29]. This SIIstimulated signaling affirms that the conformations of the β-arrestin coupling receptor and the G-protein-activating receptor are distinct [8]. In contrast, β-arrestin's effects in isolated adult mouse cardiomyocytes suggested that, in isolated cardiac myocytes, the contraction of β-arrestin signaling is induced via SII, indicating the cardiac role of βarrestin-biased ligands [30].…”
Section: Side Effects Of Conventional Antihypertensive Drugs and An Insight On The Process Of New Cardiac Drug Discoverysupporting
confidence: 58%
“…Non-renin enzymes like cathepsin and tonin also interact with angiotensinogen directly to produce Ang II. Ang II is further affected by proteolytic cleavages that produce angiotensin III (Ang III) or Ang-(2-8) and angiotensin IV (Ang IV) or Ang (3)(4)(5)(6)(7)(8).…”
Section: Effects Of β-Arrestin1 and β-Arrestin2 On The Renin-angiotensin-aldosterone Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify such members in the family with the condition, the physician may request for family history of hypertension. From the history that the family gives if either of the parents or both; uncle or aunt has hypertension that without a doubt raises suspicion for greater risk [12]. Apart from digging into the family history and possible hypertension, the physician can also consider the family's sleeping habits.…”
Section: The Role Of a Family Physician In The Diagnosis And Management Of Hypertensionmentioning
confidence: 99%